How Social Media and Behavioral Intention Enhances Customer Loyalty - Ayamolowo, Olalekan Kayode (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Social media is a powerful tool for globalization, commerce and organization profitability. Thus, with help of internet and Web 2.0, that induced the outburst of social media in this present business world, and amplified the understanding and necessity of having loyal customers for product and services, eventuated research interest towards finding if social media usage enhances customers’ loyalty. Therefore the purpose of this study is to research if organization involvement in Social media can enhance customers’ loyalty, also, to find out if social presence affects behavioral intention, and if behavioral intention having positive impact on customer loyalty. Both quantitative and measurable method to data gathering and assessment was adopted for the procedural basis of this study. Eastern Mediterranean University Students, who uses either iPhone, Samsung or other brand, and also, that understand social media usage were the sample for this study. Surveys were distributed to examine their opinion concerning respondents’ phone brand and the company social media activities. Total number of 222 questionnaires were retrieved, while SPSS statistical analysis was conducted for necessary reliability test for the scale, as well as confirmatory factor analysis, correlation and regression analysis. The research findings demonstrated a good understanding of social media, how it can be used to achieve organization goal, and how social media can be utilized to enhance customer loyalty. However, result reveals that social presence and behavioral intention does have positive effect on customers’ loyalty. Also, it was established that social presence has predictive positive effect on behavioral intention. The study shows social media presence, behavioral intention are two essential points in terms of forming customer loyalty for mobile phone industries. Due to interactive nature of social media, that promotes relationships, sharing information, as well as its immense popularity, that captures large number of customers across the globe, makes it undoubtedly important for an organization profitability and sustenance. The study however, provides further enthralling indication that social media is an active means to engage public and customer for purchase intention-related behavior. The study concludes by presenting various suggestions that mobile phones industry can use social media platform generate friendly environments, achieve and maintain customers’ loyalty for their product. The limitations associated with this study is the fact that Social Presence and Behavioral Intention explained little variation in Customers’ Loyalty means the model need to be empirically investigated more rigorously, including other factors that aids customers’ loyalty. More so, a larger sample, and data collected across locations, these will give a more explicit analysis and assessment of customer loyalty and social media and further strengthen the results.

ÖZ: Sosyal medya, küreselleşme, ticaret ve organizasyon karlılığı için güçlü bir araçtır. Dolayısıyla, bu interaktif iş dünyasında sosyal medyanın patlamasına neden olan internet ve Web 2.0'ın yardımıyla, ürün ve hizmetler için sadık müşterilerin bulunmasının öneminin daha iyi anlaşılması ve sosyal medya kullanımının müşterilerin sadakatini arttırıp arttırmadığını araştırmaya karar verildi. Bu nedenle, bu araştırmanın amacı, sosyal medyadaki örgüt katılımının, müşterilerin sadakatini artırabileceğini araştırmak ve aynı zamanda, toplumsal varlığın davranış niyetini, davranış sadakati ve müşteri sadakati üzerindeki pozitif etkilerini bulmak için araştırma yapmaktır. Araştırmanın metodolojik temelini hem verilerin toplanmasına ve yorumlanmasına yönelik niceliksel ve niceliksel yaklaşımda araştırmanın metodolojik temelini oluşturmaktadır. Bu çalışma Doğu Akdeniz Üniversitesi’nde iPhone, Samsung veya diğer marka kullanan öğrencilerin sosyal medya kullanımını anlamanın bir örneklemiydi. Katılımcıların telefon markası ve şirket sosyal medya faaliyetleri hakkındaki görüşlerini incelemek üzere anketler dağıtıldı. Toplam 222 anket formu alınırken, ölçek için gerekli güvenilirlik testi ve doğrulayıcı faktör analizi, korelasyon ve regresyon analizi için SPSS istatistiksel analizi yapılmıştır. Bu çalışmanın bulguları, sosyal medyanın iyi bir şekilde anlaşıldığını, organizasyonun hedefini gerçekleştirmek için nasıl kullanılabileceğini ve müşteri sadakatini artırmak için sosyal medyadan nasıl yararlanılabileceğini gösterdi. Bununla birlikte, sonuçlar sosyal varlığın ve davranış niyetinin müşterilerin sadakatini olumlu etkilediğini ortaya koymaktadır. Ayrıca, sosyal varlığın davranışsal niyet üzerinde tahmini pozitif etki yaptığı saptanmıştır. Çalışma, sosyal medya varlığının, davranış niyetinin, cep telefonu endüstrileri için müşteri sadakati oluşturma açısından iki önemli faktör olduğunu gösteriyor. Sosyal medyanın etkileşimli yapısı nedeniyle, ilişkileri teşvik eden, bilgi paylaşımı ve geniş çaplı popülaritesi, dünya genelinde çok sayıda müşteriyi yakalaması, bir organizasyonun kârlılığı ve beslenmesi için kuşkusuz önemli. Ancak bu çalışma, sosyal medyanın niyetinin ilişkili, davranış , satın alma söz konusu olduğunda etkin bir araç olduğunun daha güçlü kanıtlarını ortaya koymaktadır. Çalışma, cep telefonu endüstrisinin sosyal ortam platformu kullanarak dostane ortamlar oluşturabileceği, müşterilerin ürünlerine olan sadakatini sağladığı ve sürdürdüğü çeşitli önerileri sunarak sonuçlandırıyor. Bu çalışmayla ilgili sınırlamalar, Sosyal Varlık ve Davranış Niyetinin Müşterilerin Bağlılıklarındaki küçük farklılıkları açıkladığı gerçeğidir; bu da, modelin müşterilerin sadakatine yardımcı olan diğer faktörler de dahil olmak üzere ampirik olarak daha kapsamlı bir şekilde araştırılması gerektiği anlamına gelir. Daha da önemlisi, daha büyük bir örnek ve yerlerde toplanan veriler, müşteri sadakati ve sosyal medyayı daha ayrıntılı bir şekilde analiz etmeye ve sonuçları daha da güçlendirebilir.
Master of Business Administration in Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2017. Supervisor: Prof. Dr. Mustafa Tümer.
Keywords: Business Administration; Social Media--Customer Loyalty; Social Media; Behavioral Intention; Customer loyalty